Effect of Benzoic Acid and Essential Oil Blends on Viral Load in Swine Feed and Vitamin Premix - Allison K. Blomme; Jordan T. Gebhardt; Cassandra K. Jones; Jason C. Woodworth; Elizabeth Poulsen Porter; Jianfa Bai; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2021)
Feed has been shown to harbor viable virus of interest to swine producers over an extended period of time. The use of mitigants and kill steps have been investigated with variable results. This study investigated the use of benzoic acid (BA) and an essential oil blend (EO) to mitigate the presence of porcine epidemic diarrhea virus (PEDV), porcine reproductive and respiratory syndrome virus (PRRSV), and Senecavirus A (SVA) in a complete diet (Exp. 1) and a vitamin premix (Exp. 2). Four treatments consisting of 0.5% BA; 0.5% BA and 200 ppm EO; 0.3% BA and 120 ppm EO; and 0.25% BA and 100 ppm EO were used in the complete feed, in addition to a control with no feed additive to test the mitigant’s effect on PEDV, PRRSV, and SVA detection. For Exp. 2, a vitamin premix without chemical treatment acted as the control and the other treatment was the vitamin premix treated with 2.68% EO, with both used to determine PEDV detection. The inoculated feed or premix was stored for up to 15 d with sampling points at 2, 5, and 15 d post-inoculation. Samples were analyzed using a triplex qRT-PCR to detect changes in RNA quantities for all three viruses. A significant treatment × day interaction was observed in the feed for both PEDV (P= 0.008) and SVA (P<0.001). Per the decreased cycle threshold (Ct) value, the 0.5% BA treatment had higher (P<0.05) measurements of detectible PEDV on d 2 and 5, and lower amounts of detectible PEDV on d 15, as compared to the control. The 0.5% BA treated feed had lower (P<0.05) detectable SVA on d 2 but higher detectible SVA on d 15 compared to the control. There was no evidence of difference in detectable PRRSV between treatments. During this experiment, PEDV and SVA showed a degradation over time with rates of degradation varying between treatments. Increasing time from d 2 to 15 decreased (quadratic, P = 0.038) detectable PRRSV. The use of the EO in the vitamin premix had no evidence of a treatment × day interaction, treatment effect, or degradation over time. In conclusion, the use of 0.5% BA had an increased PEDV Ct on d 15 compared to the control (33.8 vs. 32.7 Ct, respectively). However, the use of BA and EO mitigant in this model did not provide consistent evidence for increased viral degradation, but viral load was reduced in the feed matrix over time.
Keywords: Feed mitigant; virus in feed; benzoic acid; essential oils